Continuous flow heterogeneous catalytic reductive aminations under aqueous micellar conditions enabled by an oscillatory plug flow reactor. Issue 15 (14th July 2021) - Wernik, Michaela; Sipos, Gellért; Buchholcz, Balázs; Darvas, Ferenc; Novák, Zoltán; Ötvös, Sándor B.; Kappe, C. Oliver
Abstract : An oscillatory plug flow reactor that combines active and passive mixing enables heterogeneous catalytic reductive aminations under aqueous micellar conditions in an inherently scalable manner. Abstract : Despite the fact that continuous flow processing exhibits well-established technical advances, aqueous micellar chemistry, a field that has proven extremely useful in shifting organic synthesis to sustainable water-based media, has mostly been explored under conventional batch-based conditions. This is particularly because of the fact that the reliable handling of slurries and suspensions in flow has been considered as a significant technical challenge. Herein, we demonstrate that the strategic application of an oscillatory plug flow reactor enables heterogeneous catalytic reductive aminations in aqueous micellar media enhancing mass transport and facilitating process simplicity, stability and scalability. The micellar flow process enabled a broad range of substrates, including amino acid derivatives, to be successfully transformed under reasonably mild conditions utilizing only very low amounts of Pd/C as a readily available heterogeneous catalyst. The preparative capabilities of the process along with the recyclability of the heterogenous catalyst and the aqueous reaction media were also demonstrated.